Gambier (Uncaria gambir Roxb.) Plant Productivity Relation Based On Growing Altitude In Lima Puluh Kota Regency - Sukma Rela; Evi Sribudiani; Viny Volcherina Darlis (Jurnal Ilmu Ilmu Kehutanan, 2023)
Gambier cultivation location is usually carried out on sloping land which results in decreased land carrying capacity due to soil erosion. This research was to determine whether the factors of altitude and slope are related to the production of gambier plants and other factors related to gambier production. This research was conducted in Lima Puluh Kota Regency, West Sumatra in September 2020. The data collection methods is to use the interview method, observation and document study. Interview and observation methods were used to obtained gambier production data, gambier harvesting, gambier processing, general conditions of the research location, visual appearance of soil erosion, height of the gambier growing area, topography and soil type. Indirect data were collected using the document study method. The selection of informants was carried out by purposive sampling with a total of 10 people. Data analysis used qualitative descriptive analysis by linking the informants 'answers with document studies, then doing a description in the form of gambier production as outlined in the informants' responses. Altitude has no relation to the production of gambier, but the factors of price, treatment process, soil type and the choice of mixed plant species are factors related to gambier production in Lima Puluh Kota Regency. The slope factor has no relation to the production of gambier in Lima Puluh Kota Regency. Land owners still observe the principles of soil and water conservation by applying mulch (ground cover) from the dregs of gambier and conducting mixed planting with seasonal and annual plant types.